Source and Trap Elements of Petroleum System Analogue Study, Along Cameron Highland - Gua Musang Road - Bin Azhar, Muhammad Zulhelmi (Universiti Teknologi PETRONAS, 2016)
This project is about the study of source and trap formation in Gua Musang Formation, focusing on Pos Blau, Gua Musang, Kelantan. Gua Musang Formation predominantly known for crystalline limestone, interbedded with thin beds of shale, tuff, chert nodules and subordinate sandstone. This research will provide geological study of the area as well as providing a geological map of the study area. The study also will provide rose diagram analysis for stress analysis, Total Organic Carbon (TOC) analysis to study total carbon content and analogue study of vitrinite reflectance data from Malay Basin. Last but not least, source and trap formation in Gua Musang Formation is also discussed.